Carbapenem resistance gene blaNDM-1 in Escherichia coli, Serratia marcescens and Klebsiella michiganensis strains from a pediatric patient - Yuanyuan Li; Xiangkun Zeng; Mi Zhou; Yi Liu; Chen Xu; Xiaofan Li; Yunbing Li; Lili Huang; Ning Dong (Journal of Infection and Public Health, 2025)
Carbapenem resistance has a widespread globally. In this study, three bacterial strains including Escherichia coli (SXY-EC), Serratia marcescens (SXY-SM), and Klebsiella michiganensis (SXY-KM) were isolated from a pediatric patient in China. Whole-genome sequencing and resistome analysis revealed the appearance of blaNDM-1 β-lactamase gene in all these three strains, and conjugation tests confirmed its transferability. Additionally, SXY-SM and SXY-KM harbored two to three other resistance genes, while SXY-EC carried eleven. Notably, the multidrug resistance region containing blaNDM-1 in plasmid pSXY-EC_NDM1 from SXY-EC was flanked by mobile elements, potentially enabling intermolecular replicative transposition mediated by distinct insertion sequences.